2018
DOI: 10.1186/s40364-018-0142-y
|View full text |Cite
|
Sign up to set email alerts
|

SRSF2 mutations in myelodysplasia/myeloproliferative neoplasms

Abstract: Recurrent gene mutations have been described with varying frequencies in myelodysplasia (MDS) /myeloproliferative neoplasm (MPN) overlap syndromes (MMOS). Recent work has placed significant focus on understanding the role of gene lesions involving the spliceosomal machinery in leukemogeneis. SRSF2 is a gene encoding critical spliceosomal proteins. SRSF2 mutations appear to play an important role in pathogenesis of MMOS, particularly in chronic myelomonocytic leukemia. Inhibition of splicing may be a new therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…For instance, point mutations and deletions in the HNRNPK gene, causing hnRNP K down-regulation, have been suggested to have a role in the development of acute myeloid leukemia (Sweetser et al, 2005;Gallardo et al, 2015). Moreover, hotspot mutations in the SRSF2 gene, such as P95H, change the binding properties of the SRSF2 protein and cause genome-wide splicing network alteration and aberrant maturation of different hnRNPs, including HNRNPA2B1, HNRNPM, HNRNPH1, and HNRNPH3, especially in myelodysplastic syndromes (Komeno et al, 2015;Arbab et al, 2018;Aujla et al, 2018;Liang et al, 2018;Masaki et al, 2019).…”
Section: Thementioning
confidence: 99%
“…For instance, point mutations and deletions in the HNRNPK gene, causing hnRNP K down-regulation, have been suggested to have a role in the development of acute myeloid leukemia (Sweetser et al, 2005;Gallardo et al, 2015). Moreover, hotspot mutations in the SRSF2 gene, such as P95H, change the binding properties of the SRSF2 protein and cause genome-wide splicing network alteration and aberrant maturation of different hnRNPs, including HNRNPA2B1, HNRNPM, HNRNPH1, and HNRNPH3, especially in myelodysplastic syndromes (Komeno et al, 2015;Arbab et al, 2018;Aujla et al, 2018;Liang et al, 2018;Masaki et al, 2019).…”
Section: Thementioning
confidence: 99%
“…10 The use of other molecular targeted therapy such as SRSF2 inhibitor may be necessary to overcome primary resistant to the KIT inhibitor. 17,18 In conclusion, our study has demonstrated the clonal evolution of malignant cells during the progression of ASM-CMML under treatment with midostaurin and azacitidine and provided a rationale for the combinatorial molecular targeted therapy in advSM.…”
Section: Genomic Testing Was Approved By the Mackay Memorial Hospitalmentioning
confidence: 68%
“…Loss of ASXL1 leads to an increase in apoptotic and proliferating cells, but also reduced HSC and progenitor populations (Wang et al, 2014). Mutations in the SRSF2 gene lead to growth arrest, early senescence and apoptosis in hematopoietic cells (Aujla, Linder, Iragavarapu, Karass, & Liu, 2018). These mutations combined could explain the distinct pattern of proliferative aberrancies seen in the MDS/MPN cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the SRSF2 gene lead to growth arrest, early senescence and apoptosis in hematopoietic cells (Aujla, Linder, Iragavarapu, Karass, & Liu, 2018). These mutations combined could explain the dis- F I G U R E 3 Summary of basic characteristics and Ki-67 expression of myeloid BM malignancies.…”
Section: The Ki-67 Expression Pattern In Mds Patientsmentioning
confidence: 99%